Asymmetric Synthesis of Contact Pheromone Component of Xylotrechus colonus and Its Analogues. Issue 13 (4th April 2023) - Yuan, Chaonan; Wu, Jianwei; Yu, Shihang; Bian, Qinghua; Wang, Min; Liu, Dan; Zhong, Jiangchun
Abstract: Xylotrechus colonus is an abundant wood‐boring pest of woody plants. 3‐Methylpentacosane was identified as the component of its contact pheromone. A novel and efficient asymmetric synthesis of ( S )‐3‐methylpentacosane and its analogues was developed using ( S )‐2‐methylbutan‐1‐ol as chiral source. The key of this approach included Wittig coupling of chiral phosphonium salt with aldehyde, Pd‐catalyzed hydrogenation and Appel reaction. Our synthesis would be helpful for the control and detect of this pest. Abstract : A novel and efficient asymmetric synthesis of a contact pheromone component of Xylotrechus colonus, ( S )‐3‐methylpentacosane, and its analogues ( S )‐3‐methylheptacosane and ( S )‐3‐methylnonacosane was developed using ( S )‐2‐methylbutan‐1‐ol as chiral source. The key steps of this approach included Wittig coupling of chiral phosphonium salt with aldehyde, Pd‐catalyzed hydrogenation and Appel reaction.